2016
DOI: 10.1038/srep39164
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational density of states and thermodynamics at the nanoscale: the 3D-2D transition in gold nanostructures

Abstract: Surface enhanced Raman scattering (SERS) is generally and widely used to enhance the vibrational fingerprint of molecules located at the vicinity of noble metal nanoparticles. In this work, SERS is originally used to enhance the own vibrational density of states (VDOS) of nude and isolated gold nanoparticles. This offers the opportunity of analyzing finite size effects on the lattice dynamics which remains unattainable with conventional techniques based on neutron or x-ray inelastic scattering. By reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 49 publications
(140 reference statements)
2
40
0
Order By: Relevance
“…Indeed, surface-sensitive phonon spectroscopy has demonstrated a reduction of the Debye temperature due to the presence of the surface and the resulting change in bonding geometry [30][31][32]. In nanowires, the surface-to-volume ratio is large and therefore, the reduction of the surface Debye temperature may affect the Bloch-Grüneisen resistivity.…”
Section: The Tcr Methods In Metallic Nanowiresmentioning
confidence: 99%
“…Indeed, surface-sensitive phonon spectroscopy has demonstrated a reduction of the Debye temperature due to the presence of the surface and the resulting change in bonding geometry [30][31][32]. In nanowires, the surface-to-volume ratio is large and therefore, the reduction of the surface Debye temperature may affect the Bloch-Grüneisen resistivity.…”
Section: The Tcr Methods In Metallic Nanowiresmentioning
confidence: 99%
“…At first, some well‐defined lines at low wavenumber are ascribed to Lamb modes of the AgNCs. They are superimposed to a rather continuous signal in which we extract the second and third contributions: a poorly structured contribution below 170 cm −1 that we will assign to Ag bulk phonons and a background (gray area in Figure ), which intensity decreases monotonously with wavenumber. This last contribution is certainly due to fluctuations among the smooth assembly of ligands as its unstructured shape is characteristic of a viscous medium: It will be not discussed in this work and indeed simply treated as a background.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently shown that the VDOS gives a signature of the atomic arrangements, and the best agreement between the calculated and the measured VDOS is obtained for the ICO morphology for small AgNCs embedded in SiO 2 . To access information about the VDOS of the present samples, we have used the experimental procedure based on plasmon‐enhanced Raman scattering for small metallic nanostructures . The only exploitable data were obtained with supercrystals of Type A (〈 D 〉 = 4.3 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations